Electrochemical determination of the glass transition temperature of thin polyelectrolyte brushes at solid liquid interfaces by impedance spectroscopy - Alonso García, Teodoro (2013)
Devising strategies to assess the glass transition temperature (Tg) of polyelectrolyte assemblies at solid-electrolyte interfaces is very important to understand and rationalize the temperature-dependent behavior of polyelectrolyte films in a wide range of settings. Despite the evolving perception of the importance of measuring Tg under aqueous conditions in thin film configurations, its straightforward measurement poses a challenging situation that still remains elusive in polymer and materials science. Here, we describe a new method based on electrochemical impedance spectroscopy (EIS) to estimate the glass transition temperature of planar polyelectrolyte brushes at solid?liquid interfaces. To measure Tg, the charge transfer resistance (Rct) of a redox probe diffusing through the polyelectrolyte brush was measured, and the temperature corresponding to the discontinuous change in Rct was identified as Tg. Furthermore, we demonstrate that impedance measurements not only facilitate the estimation of Tg but also enable a reliable evaluation of the transport properties of the polymeric interface, i.e., determination of diffusion coefficients, close to the thermal transition. We consider that this approach bridges the gap between electrochemistry and the traditional tools used in polymer science and offers new opportunities to characterize the thermal behavior of complex polymeric interfaces and macromolecular assemblies.